Evaporation measurement from free water surface - Thanh, Huyen Dao Thi; Dolezal, Frantisek; Mori, Yasushi (Vietnam Journal of Science and Technology, 2020)
This paper aims to quantify the amount of water surface evaporation with special regard to the EWM evaporation pan and to relate the direct measurements to the Penman and other empirical equations. Based on the available 10-minute interval data on the EWM pan evaporation and the data on precipitation for the same intervals, the net water surface evaporation was estimated for the period from July 2010 to October 2012 (excluding the time EWM pan did not function in winter). From the processing data, raingauge appeared to underestimate the actual precipitation on average 5:3 times, and malfunction when heavy rains occurred. Thus, the net evaporation was estimated only from the fluctuation of water level in EWM pan. Other available weather data, including the dry/wet bulb temperature, water surface temperature, air humidity, wind speed and short-wave solar radiation were also summarized and corrected. These data were then used as input for the Penman equations to obtain semi-empirical daily values of evaporation from water surface. A comparison between the evaporation rates directly measured and those calculated by different methods shows that different values of albedo would improve the performance of the Penman equations. The result of this study contributed to optimization of the EWM data processing methods and to the analysis of variation of water surface evaporation within the diurnal cycle, as well as over longer periods.